Syn-to post-orogenic mineralization in the Shuangkoushan Au–Ag–Pb deposit, North Qaidam: insights from H–O–S isotopes and U–Pb geochronology - Yu, Junzhen; Li, Dexian; Zheng, Youye; Ma, Bo; Wang, Jian; Shi, Guomei; Xu, Rongke; Khan, Junaid; Tahir, Asma (Frontiers in Earth Science, 2025)
The Shuangkoushan Au–Ag–Pb deposits, hosted within meta-basaltic rocks of the Tanjianshan Group in the North Qaidam Orogenic Belt, northwest China, present significant insights into syn-to post-orogenic mineralization processes. Preliminary fluid inclusion studies suggest distinct fluid origins for Ag–Pb and Au mineralization at Shuangkoushan; however, due to the lack of geochronological and isotopic data, as well as comprehensive textural analysis, this hypothesis remains unverified. This research aims to identify the orogenic phase associated with the Shuangkoushan Au and Ag-Pb ore deposits and to constrain the potential sources of the fluid and ore-forming materials through detailed microscopic investigations, zircon U-Pb dating, and H–O–S isotopic analyses. The syn-orogenic meta-basaltic rocks, intruded by gabbros, host numerous orogenic Au deposits and are structurally controlled by a NW–SE-trending ductile shear zone. The contact morphology indicates proximal emplacement of both igneous units, with the influence of the ductile shear zone evident in each assemblage. Geochronological analysis using zircon U–Pb dating of the gabbroic pluton yields a Concordia age of 206Pb/238U = 448.5 ± 2.5 Ma, which likely predates the formation of the ductile shear zone/quartz veins and provides critical temporal constraints on the Au mineralization sequence. The Au mineralization stage characterized by fluid isotopic compositions (δDV-SMOW = −72.9‰ to −81.5‰; δ18OH2O-SMOW = 3.45‰–4.95‰; δ18OV-SMOW = 10.4‰–13.9‰) and pyrite sulfur isotopes (δ34S = +4.8‰ to +10‰), indicating predominantly metamorphic fluids mixed with substantial meteoric water and a basalt-derived metal source. The Ag-Pb ore body formed in association with post-orogenic deep magmatism in late Devonian, rather than the adjacent Neoproterozoic granitic gneisses (206 Pb/238U = 835 ± 6.3 Ma, 924 ± 6.3 Ma). The Ag-Pb mineralization stage shows H-O (δDV-SMOW -108.2‰ to −113.8‰, δ18OH2O-SMOW 6.45‰–6.55‰, δ18OV-SMOW 14.1‰–14.3‰) and S-isotopic (δ34S + 0.2‰ to +3.3‰) compositions, suggesting that Ag-Pb mineralizing fluids were primarily sourced from primitive magmatic water with a minor meteoric water component, and Ag-Pb ore-forming materials were primarily sourced from deep magmatic source. Field geological features, isotopic data, and orogenic deposits comparisons, indicate that the Shuangkoushan Au-Ag-Pb deposit formed through Syn-to Post-orogenic mineralization stages.